THE RADIAL INCREMENT DYNAMICS OF MIDDLE-AGED PINE FORESTS DAMAGED BY SURFACE FIRES IN THE GREEN ZONES OF KHARKIV CITY - Melnyk, Ye. Ye. (Forestry and Forest Melioration, 2018)
Introduction The reaction of middle-aged pine forest stands to the impact of fires depends not only on the nature and intensity of the fire, but also on the weather conditions in certain years, as well as on peculiarities of soils and characteristics of trees by themselves. Annual tree rings reflect the influence of changes in external environmental conditions on their formation. Therefore, the radial increment can serve as a biological indicator and enable researchers to study the development of woodlands affected by fires, as well as to trace the regeneration or further degradation processes in the stands. The aim of the study was to analyze the changes in the radial increment in the middle-aged pine stands after they were damaged by the surface fire in 2009 and over the post-fire period (5 years) as well as to compare them with the main weather indicators during the growing season in order to find out how these factors influence the radial increment. Materials and Methods The permanent sample plots established in the pine forests damaged by a spring fire with different intensity were the object of the study. To do research, we applied the standard dendrochronology methods. By means of Pressler borer we selected core (20–25 pieces) from a tree trunk at the height of 1.3 m. Then we analyzed the sizes of annual rings and layers of spring and summer wood. In addition, we carried out the qualitative analysis, namely we compared the graph describing the increment dynamics and that describing the climate data during the growing season for a long period. Results We thoroughly analyzed the consequences of the fire and found out that the condition of pine forests deteriorated significantly as early as in the year of the fire. The health condition index in the stands at all sample plots ranged from 2.73 to 3.19. Thus, the stands were estimated as much weakened. On comparing the increment among groups of trees with different height of bark char during 2004–2013, we discovered that the annual radial increment of the pine trees in the most of years for nearly all damaged stands even exceeded control before the fire in 2009. In addition, we found out that after the fire damage in spring 2009 the radial growth fell only on the damaged sample plots. Similar small increments for damaged trees and controls were observed in 2011 and 2012. That points at the fact that not only fire may affect the changes in growth, but other factors as well, adverse weather conditions, in particular The changes in the radial growth of spring and summer wood for all three selected groups of trees with different height of bark char decreased as early as in 2009. No dependence of the growth rate on the height of the bark char in that case was detected. In control no significant difference in increment was observed comparing with the previous year. Significant decrease of this indicator both among damaged trees and in control was recorded in 2010 and during the next 3 years. The fluctuation of these indicators during that period was negligible. Conclusions Taking into the account the fact that the increase of the radial increment among groups of trees with different height of bark char and in control during the post-fire years was similar, we came to the conclusion that the weather conditions were the main factor of the changes. It is worth to mention that during the years from 2010 to 2013 extremely unfavourable arid weather conditions were registered throughout nearly all the growing season. The reduction of the radial increment was severely affected by both the adverse effects of the fire and the weather conditions (quantitatively expressed by the deviations of the mean temperature and precipitation during the growing season from the long-term norm). During the years with a small amount of precipitation, the radial growth decreases synchronously, both in damaged and control trees. 3 Figs., 6 Tables, 19 Refs.